2013
DOI: 10.1310/hpj4810-834
|View full text |Cite
|
Sign up to set email alerts
|

Survey and Systematic Literature Review of Probiotics Stocked in Academic Medical Centers within the United States

Abstract: Background: Probiotics have a wide variation in their effectiveness in preventing or treating conditions due to the varying beneficial effects of specific probiotic strains. In other words, there is no ''generic equivalency'' between different probiotic species. However, it is has been noted that many practitioners consider probiotics in generic terms and may not realize the impact of these differences between probiotics. Objective: The aims of this study were to identify probiotics used in US academic medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This finding is comparable with the aforementioned survey of probiotic use among U.S. academic medical centers in which 10 products were identified in stock or in use across 87% of the 114 responding centers, with 79% of the centers reported stocking or using only 1 product. 10 At the species level, the top 4 probiotic products most frequently reported across the centers 10 were also similar to those used in the current study, consisting of L rhamnosus, Lactobacillus gasseri and L bulgaricus, Lactobacillus acidophilus, and S boulardii.…”
Section: Comparability With Other Studiessupporting
confidence: 63%
See 1 more Smart Citation
“…This finding is comparable with the aforementioned survey of probiotic use among U.S. academic medical centers in which 10 products were identified in stock or in use across 87% of the 114 responding centers, with 79% of the centers reported stocking or using only 1 product. 10 At the species level, the top 4 probiotic products most frequently reported across the centers 10 were also similar to those used in the current study, consisting of L rhamnosus, Lactobacillus gasseri and L bulgaricus, Lactobacillus acidophilus, and S boulardii.…”
Section: Comparability With Other Studiessupporting
confidence: 63%
“…9 A recent survey of U.S. academic medical centers found 87% of 114 respondents stocked or used at least 1 probiotic, with a total of 10 probiotic products among the centers. 10 In a separate study in an academic medical center, 0.4% of patients were prescribed a probiotic in 2007-2008, with 96% of these patients receiving a combination product (L acidophilus-Lactobacillus bulgaricus) and 4% receiving a product containing Saccharomyces boulardii. 11 Prevention and treatment of CDI, treatment for unspecified diarrhea, and prevention of AAD comprised 78.3% of the justifications for probiotic use in this center.…”
mentioning
confidence: 99%
“…However, another study found probiotics to be a significant risk factor for Vancomycin-resistant Enterococcus colonization and was suggested to mediate the acquisition and transfer of resistance genes of bacteria 14 . Despite this, surveys have shown that clinicians and naturopaths recommend probiotic consumption for patients with a variety of pathologies including diarrhea, ulcerative colitis, and infant colic due to their low cost, over-the-counter availability, and acceptable safety profile in healthy adults 15 18 . The typical probiotic strains manufactured include Bifidobacterium and lactic acid bacteria such as Lactobacillus species.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of growing public interest, and despite outdated SHEA/IDSA guidelines 26 deterring the clinical use of probiotics in CDI due to “insufficient evidence”, clinicians are making general recommendations to patients on antibiotic therapy. 5254 The World Gastroenterology Organization Global Guidelines 55 concur that there is strong evidence showing the efficacy of specific probiotics at preventing CDI, but agree with the FDA and others that more evidence based on randomized, placebo-controlled, blinded studies is required before specific products can be ranked with proven efficacy.…”
Section: What the Experts Saymentioning
confidence: 99%
“…Extensive use of probiotics by physicians and patients in the absence of clear recommendations 5254,56 was the basis for founding the Yale University Workshop on Probiotic Recommendations that assesses the scientific literature regarding the efficacy of probiotics. This panel of probiotic experts consistently reports that the literature substantiates the use of probiotics in the case of antibiotic-associated diarrhea.…”
Section: What the Experts Saymentioning
confidence: 99%